Early Immersive Culture Mixing: The Key to Understanding Cognitive and Identity Differences Among Multiculturals. (November 2016) - Martin, Lee; Shao, Bo
Why some multicultural individuals think and identify differently to others is a question that is yet to be clearly answered. We suggest that a key antecedent to psychological differences among multiculturals is early immersive culture mixing, or experiencing multiple cultures simultaneously at home while growing up. We propose that innate multiculturals (defined as individuals who have experienced early immersive culture mixing) are cognitively guided by a single hybrid cultural schema and have a hybrid cultural identity. This would make them fundamentally different from achieved multiculturals (individuals who have become multicultural in other ways), who should possess multiple distinct cultural schemas and cultural identities. A quasi-experiment indicated that, as predicted, innate multiculturals were guided by a single cultural frame with respect to attribution and locus of attention, whereas achieved multiculturals switched between different cultural frames. Innate multiculturals also reported a more integrated cultural identity than did achieved multiculturals. These findings open a new avenue in multiculturalism research, with important potential implications of early immersive culture mixing for a range of individual outcomes such as creativity.